Perancangan Media Pembelajaran Berbasis Multimedia untuk Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Kamila, Naila; Annas, Firdaus; Oktavia, Susi (Yayasan Lembaga Studi Makwa, 2024)
Education in Indonesia, especially at the elementary school level, faces challenges in improving the quality of learning, especially in Indonesian language subjects. Many students experience difficulty in understanding material presented through conventional teaching methods which tend to be monotonous. This research aims to design interactive and interesting multimedia-based learning media to increase students' motivation and understanding of Indonesian language material. The designed learning media integrates visual, audio and interactivity elements to create a more enjoyable and effective learning experience. Through the development of this media, it is hoped that students can be more actively involved in the teaching and learning process, so that their learning outcomes can improve. This research also aims to make a positive contribution to the development of education in Indonesia by utilizing information technology in learning. It is hoped that the results of this research can be a reference for teachers and other educators in creating a more innovative and effective learning environment.